Lenvatinib Beyond First-Line Therapy in Patients With Advanced Biliary Tract Carcinoma - Wang, Yunchao; Yang, Xiaobo; Wang, Dongxu; Yang, Xu; Wang, Yanyu; Long, Junyu; Zhou, Jinxue; Lu, Zhenhui; Mao, Yilei; Sang, Xinting; Guan, Mei; Zhao, Haitao (Frontiers in Oncology, 2022)
Introduction: Lenvatinib, a multiple receptor tyrosine kinase inhibitors that target vascular endothelial growth factor receptors and fibroblast growth factor receptors, recently demonstrated a treatment effect in various tumors. This study evaluated the efficacy and safety of lenvatinib for patients with biliary tract cancers (BTCs) who had received ≥1 line of prior systemic anti-BTC therapy . Methods: This open-label, single-arm study included adult (≥18 years) patients with histologically confirmed BTC. Efficacy and safety were evaluated based on the Response Evaluation Criteria in Solid Tumors RECIST Version 1.1 (RECIST 1.1) and the National Cancer Institute Common Terminology Criteria for Adverse Events (CTCAE version 4.0). Changes in tumor biomarkers throughout the treatment period were recorded. Results: 41 patients received lenvatinib treatment. The ORR was 12% (95% CI: 1.7–22.7), with a median PFS of 3.8 months (95% CI: 1.3–6.3) and an OS of 11.4 months (95% CI: 6.6–16.2). Thirty-nine (95.1%) patients experienced ≥1 treatment-related adverse event. Decreasing carbohydrate antigen 19-9 (CA19-9) level predicted tumor size reduction in intrahepatic cholangiocarcinoma with a sensitivity of 77.7% and a specificity of 73.9%. Conclusions: Lenvatinib which was individualized based on the patient's weight has promising clinical activity against advanced BTC and had an acceptable safety profile. Additionally, serum biomarkers and gene sequencing may hold the potential to guide our treatment.